Spontaneous blood oxygenation level-dependent fMRI signal is modulated by behavioral state and correlates with evoked response in sensorimotor cortex: a 7.0-T fMRI study. - Donahue, M; Hoogduin, H; Smith, S; Siero, J; Chappell, M; Petridou, N; Jezzard, P; Luijten, P; Hendrikse, J (2012)
Synchrony measurements of spontaneous low-frequency blood oxygenation level-dependent (BOLD) fluctuations are increasingly being used to investigate spatial regions of functional connectivity. Although information regarding BOLD-BOLD synchrony between different regions is frequently reported, the relationship between spontaneous activity and behavioral state, and the association of spontaneous signal synchrony and evoked response, are less well characterized. The purpose of this study is to exploit the higher signal-to-noise ratio and in turn available spatial resolution at 7.0 T to understand the relationship between synchrony, measured as Pearson's R value, and amplitude, measured as signal standard deviation over time, in sensorimotor cortex for four separate behavioral states: eyes closed resting (EC), eyes open fixation (EO), EO with constant right hand fist clench (EO-F) and EO with 6 s off/6 s on (0.083 Hz) right hand finger tapping (EO-T). BOLD (TE/TR = 25/3,000 ms; 100 time points) scans were performed in healthy volunteers (7.0 T; 4 M/3 F; right-handed) at high spatial resolution = 1.6 × 1.6 × 1.6 mm3 . Results (z > 5; P < 0.05; low-pass filtering <0.067 Hz) reveal that synchrony is highest in the EC state (R = 0.35 ± 0.07) and reduces for EO (R = 0.26 ± 0.07), EO-F (R = 0.23 ± 0.07; P < 0.05), and EO-T (R = 0.12 ± 0.04; P < 0.05) conditions. Amplitude was highest in the EC condition and only reduced significantly (P < 0.05) for the EO-T condition. Synchrony within sensorimotor cortex correlated with evoked finger-tapping response magnitude (R = 0.81; P = 0.03), suggesting that spontaneous signal synchrony may be a predictor of evoked BOLD response magnitude and may account for intersubject variability in sensorimotor cortex.